MEMAHAMI PUSAT-PUSAT PERADABAN ISLAM MASA PEMERINTAHAN BANI UMAYYAH DI DAMASKUS - M. Afiqul Adib (Jurnal Media Akademik (JMA), 2024)
This study aims to delve into the Islamic civilization centers that flourished during the reign of the Umayyad Caliphate in Damascus. As a crucial capital in Islamic history, Damascus played a pivotal role in the dissemination of religion, culture, and knowledge across the Umayyad Caliphate's territories. Through a historical approach, this research traces the development of civilization centers that made Damascus the golden era of Islam during that time. A comprehensive analysis of social structure, architecture, arts, and education in Damascus provides a deeper understanding of the Umayyad Caliphate's impact on the development of Islamic civilization. The findings of this research are expected to contribute to a broader understanding of Islamic history and the valuable civilization legacy from the Umayyad period in Damascus.